2016
DOI: 10.1118/1.4954845
|View full text |Cite
|
Sign up to set email alerts
|

Variability in CT lung-nodule quantification: Effects of dose reduction and reconstruction methods on density and texture based features

Abstract: Purpose:To investigate the effects of dose level and reconstruction method on density and texture based features computed from CT lung nodules.Methods:This study had two major components. In the first component, a uniform water phantom was scanned at three dose levels and images were reconstructed using four conventional filtered backprojection (FBP) and four iterative reconstruction (IR) methods for a total of 24 different combinations of acquisition and reconstruction conditions. In the second component, raw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 19 publications
1
58
0
Order By: Relevance
“…Several studies have shown that various conditions affecting image quality significantly influence the reliability of RF measurements. For example, inconsistencies across CT scanners such as, spatial resolution, tube current, noise, and reconstruction algorithm may decrease the reliability of CT-derived RFs [9][10][11][12][13][14] . The reliability of RFs also depends on the techniques used for lesion segmentation, grey-level discretization and quantization range 8,[15][16][17][18] .…”
mentioning
confidence: 99%
“…Several studies have shown that various conditions affecting image quality significantly influence the reliability of RF measurements. For example, inconsistencies across CT scanners such as, spatial resolution, tube current, noise, and reconstruction algorithm may decrease the reliability of CT-derived RFs [9][10][11][12][13][14] . The reliability of RFs also depends on the techniques used for lesion segmentation, grey-level discretization and quantization range 8,[15][16][17][18] .…”
mentioning
confidence: 99%
“…As reducing X-ray dose is main concern in imaging, different vendors provide imaging protocols and reconstruction techniques to reduce patient dose without substantially risking the image quality. These ultra-low dose, or even low dose, settings lead to lower contrast to noise ratio, which in turn leads to higher possibility to CT artifacts and lower capability to spot diseases [51][52][53]. These parameters are relevant to any CAD system [2,3,47,48], so can greatly affect the PE CAD performance.…”
Section: Factors Affecting Ctpa-cad Performancementioning
confidence: 99%
“…This include, the supported range of equipment, CTPA image acquisition settings, patient preparation requirements, reconstruction algorithms, and patient special cases such as those with additional lung defects, among other relevant factors, that radiologist need to be aware during the use of CTPA-CAD. Additionally, in case of CTPA-CAD comparison with findings from previous CTPA scans is used to assess decisions on diagnosis, disease progression, and/or treatment effectiveness, care must be considered to match the acquisition conditions accordingly to CTPA-CAD operating manual [2,3,[47][48][49][50][51][52][53].…”
Section: Ctpa-cad Recommendationsmentioning
confidence: 99%
“…These tools have enabled the development of reconstruction pipelines that are not dependent on the availability of clinical CT scanners, can be configured to operate in high‐throughput batch modes, can incorporate simulated dose reduction techniques and therefore can produce a large collection of image datasets that represent a wide range of acquisition and reconstruction settings such as different slice thicknesses and reconstruction kernels used in wFBP. The results of these reconstruction pipelines have contributed to the growing list of investigations evaluating the robustness of quantitative imaging, radiomics, and CAD methods across a range of scanner platforms, acquisition conditions and reconstruction parameters …”
Section: Introductionmentioning
confidence: 99%
“…The results of these reconstruction pipelines have contributed to the growing list of investigations evaluating the robustness of quantitative imaging, radiomics, and CAD methods across a range of scanner platforms, acquisition conditions and reconstruction parameters. 2,[4][5][6][7][8][9] While this previous work was valuable and informative, it was limited to conventional wFBP reconstructions. Modern scanners offer advanced image reconstruction techniques that use some form of statistical or iterative reconstruction.…”
Section: Introductionmentioning
confidence: 99%